Global Employment Trends 2012. - Office, International Labour (International Labour Office, 2012)
The annual Global Employment Trends (GET) reports provide the latest global and regional estimates of employment and unemployment, employment by sector, vulnerable employment, labour productivity and working poverty, while also analysing country-level issues and trends in the labour market.